Incidence of fistula-in-ano after drainage of perianal abscess: a retrospective comparison of drainage alone versus drainage with primary fistula treatment - Kumar, M. Praveen; Ravishankar, H. R.; Niranjan, P. (International Surgery Journal, 2026)
Background: Perianal abscess is a common anorectal surgical emergency, most often resulting from cryptoglandular infection. While incision and drainage (I&D) is the standard treatment, persistence of the underlying septic focus may lead to recurrent abscess or fistula-in-ano. The benefit of performing fistulotomy or fistulectomy at the time of abscess drainage remains debated because of concerns regarding sphincter injury and functional outcomes. Methods: This retrospective comparative study included adult patients who underwent surgery for perianal or ischiorectal abscess between June 2018 and April 2023 at Sagar Hospital and Shanthi Hospital and Research Centre, Bengaluru. Patients were treated with either I&D alone (Group A) or I&D with concomitant fistulotomy/fistulectomy (Group B). Outcomes were assessed after a minimum follow-up of one year using a structured telephonic questionnaire and review of available clinical records. Results: Of 136 patients treated during the study period, 15 were lost to follow-up. The final analysis included 121 patients: 49 in Group A and 72 in Group B. Abscess recurrence occurred in 20.4% of Group A patients compared with 4.2% in Group B (p=0.0065; RR 4.9, 95% CI 1.4–17.0). Fistula-in-ano developed in 6.1% and 2.7% of patients, respectively, with no statistically significant difference (p=0.394; RR 2.2, 95% CI 0.4–12.5). Conclusions: Concomitant fistulotomy or fistulectomy at the time of abscess drainage was associated with significantly lower abscess recurrence. A selective approach to definitive fistula treatment during the index procedure may be beneficial in carefully selected patients with identifiable fistulous pathology.